1966
DOI: 10.1111/j.2044-8279.1966.tb01876.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Children's Behaviour at Home and at School

Abstract: An enquiry carried out among a random sample of children attending local authority schools in Buckinghamshire made it possible to compare information provided by the parents and teachers of over 6,000 children. This revealed that deviant behaviour at home was significantly associated with lack of academic success and also with the manifestation of behavioural disorders in school. There were, however, many children who exhibited disorders of behaviour either only at school or only at home. This suggests that an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 4 publications
(4 reference statements)
2
15
0
Order By: Relevance
“…The lack of overlap (beyond what might be expected by chance alone) between children identified as cases by different informants is a surprising result given that the reports obtained from the different informants were describing the same child and would not have been expected to be independent of one another. However, the result is consistent with the studies reported by Graham [14], and Mitchell and Shepherd [26] The use of a dimensional approach to describe childhood problems revealed a consistent pattern of children reporting the most problems, teachers reporting the fewest problems and the number of problems reported by parents being intermediate between the children and teachers. This suggests that during the second stage of data collection in epidemiological studies, if a "clinical-categorical" [ 13, p. 421 approach is employed to classify children's disorders, the weighting given to reports from different informants may determine whether or not a child meets the criterion for having a psychiatric disorder.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of overlap (beyond what might be expected by chance alone) between children identified as cases by different informants is a surprising result given that the reports obtained from the different informants were describing the same child and would not have been expected to be independent of one another. However, the result is consistent with the studies reported by Graham [14], and Mitchell and Shepherd [26] The use of a dimensional approach to describe childhood problems revealed a consistent pattern of children reporting the most problems, teachers reporting the fewest problems and the number of problems reported by parents being intermediate between the children and teachers. This suggests that during the second stage of data collection in epidemiological studies, if a "clinical-categorical" [ 13, p. 421 approach is employed to classify children's disorders, the weighting given to reports from different informants may determine whether or not a child meets the criterion for having a psychiatric disorder.…”
Section: Discussionsupporting
confidence: 92%
“…This relates, for instance, to the fact that children show different behaviour at school than at home (Mitchell and Shepherd, 1966). A 64.5% false positive percentage above cut-off for the parents* index was thus reduced to a 50.7% percentage when index scores were combined.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their important role in facilitating children's access to preventive mental health interventions, there is evidence that parents or teachers may lack confidence and/or accuracy in identifying children at risk of certain mental health problems, particularly internalizing disorders. For example, there are frequently large discrepancies between parent and child report in the identification of children's anxious or depressed symptoms (Angold et al, 1987;Mesman & Koot, 2000;Weissman et al, 1987) and there is a long history of research suggesting that teachers are less likely to detect behavioral predictors for internalizing disorders than externalizing disorders (Mitchell & Shepherd, 1966;Nicholson et al, 1999;Reynolds, 1990;Ritholz, 1959;Ritter, 1989;Weist, 1997;Wickman, 1928). Despite suggestions that parents or teachers are less accurate in identifying children at risk of developing internalizing disorders than externalizing disorders, this has not been directly confirmed.…”
mentioning
confidence: 95%